Determinants of User Intention toward IT Instruction: an Examination of Internal and External Factors - Show-Hui S. Huang; Wen-Kai K. Hsu (Knowledge Management & E-Learning: An International Journal, 2009)
This paper discusses the internal and external factors that affect user intention to apply IT instruction. The internal factors were examined from the standpoint of user attitudes toward IT instruction, which included computer knowledge, perceived usefulness, and interest in applying IT instruction, while external factors included climate, school policy, facility, and training in IT instruction. The effects of participant demographics were also investigated. As an empirical study, 141 valid science and technology university teachers in Taiwan were surveyed for their experiences with teaching websites. The results indicate that all of the internal factors significantly affect teacher intention to apply IT instruction, but none of the external factors do, except for the climate variable. The results may help school administrators in promoting IT instruction.